JavaFX™ Script: Dynamic Java™ Scripting for Rich Internet/Client-Side Applications - Weave, James L. (Apress, 2012)
At the annual JavaOne conference in May 2007, Sun Microsystems announced a new product family named JavaFX. Its stated purpose includes enabling the development and deployment of content-rich applications on consumer devices such as mobile phones, televisions, in-dash car systems, and browsers. According to Sun, the vision of the JavaFX product family is to deliver “the ability to create interactive content, applications and services from the desktop to mobile devices to the living room.” The JavaFX product family currently consists of two technologies: JavaFX Mobile and JavaFX Script.